Long noncoding RNA XIST expedites metastasis and modulates epithelial–mesenchymal transition in colorectal cancer - Chen, Dong-liang (Cell Death Dis, 2017)
Tumor progression and metastasis is the main cause of death in colorectal cancer (CRC). Long noncoding RNAs (lncRNAs) are critical regulators in various diseases including human cancer. In this study, we found that lncRNA XIST was overexpressed in CRC cell lines and tissues. High expression of lncRNA XIST was associated with adverse overall survival in CRC patients. Knockdown of lncRNA XIST remarkably inhibited CRC cell proliferation, invasion, epithelial–mesenchymal transition (EMT) and CRC stem cell formation in vitro as well as tumor growth and metastasis in vivo. Further study indicated that knockdown of lncRNA XIST markedly increased the expression of microRNA-200b-3p (miR-200b-3p) that has been found to be downregulated in CRC tissues and cell lines, and luciferase activity assay indicated that lncRNA XIST could bind directly with miR-200b-3p. Moreover, knockdown of lncRNA XIST significantly reduced the expression of ZEB1, which was the direct target of miR-200b-3p, and the tumor suppressive effects caused by knockdown of lncRNA XIST could be rescued by re-expression of ZEB1 in CRC cells. Overall, our study demonstrated how lncRNA XIST regulates CRC progression and metastasis by competing for miR-200b-3p to modulate the expression of ZEB1. lncRNA XIST may be used as a biomarker to predict prognosis in CRC patients.